Metaphylaxy Of Urolithiasis Disease In Children With Renal Form Of Primary Hyperparathyroidism (Texas Journal of Medical Science, 2024)
The conducted metaphylactic measures including medication and dietary measures in 52 children with ULD of PGPT genesis allowed to increase the efficiency of surgical treatment of urolithiasis and primary hyperparathyroidism. A significantly low rate of recurrent stone formation in patients who fulfilled the recommendations in full compared to those who fulfilled them partially or not at all was registered. Metaphylactic measures were carried out individually for each child depending on the etiopathogenesis and complications of the disease. A diet low in fat and sodium (table salt) was prescribed; this was the safest for normal calcium intake without increasing the risk of nephrolithiasis (for the growing organism).